Inspired by Malaysian architectural / Muhammad Shafiq Mahadi - Mahadi, Muhammad Shafiq (2022)
This Jewellery box inspired by Kampung Laut Mosque (Malay: Masjid Kampung Laut) is one of the oldest mosques in Malaysia. There is no confirmatory evidence when the building of the mosque took place. It is estimated to have been built sometime in the 15th century or 18th century. It is location on Jalan Kuala Krai, in Nilam Puri, in the Malaysian State of Kelantan.